Effect of Late Gadolinium Enhancement on the Recovery of Left Ventricular Systolic Function After Pulmonary Vein Isolation. Issue 9 (26th September 2016) - Addison, Daniel; Farhad, Hoshang; Shah, Ravi V.; Mayrhofer, Thomas; Abbasi, Siddique A.; John, Roy M.; Michaud, Gregory F.; Jerosch‐Herold, Michael; Hoffmann, Udo; Stevenson, William G.; Kwong, Raymond Y.; Neilan, Tomas G.
Abstract : Background: The factors that predict recovery of left ventricular (LV) systolic dysfunction among patients with atrial fibrillation (AF) are not completely understood. Late gadolinium enhancement (LGE) of the LV has been reported among patients with AF, and we aimed to test whether the presence LGE was associated with subsequent recovery of LV systolic function among patients with AF and LV dysfunction. Methods and Results: From a registry of 720 consecutive patients undergoing a cardiac magnetic resonance study prior to pulmonary vein isolation (PVI), patients with LV systolic dysfunction (ejection fraction [EF] <50%) were identified. The primary outcome was recovery of LVEF defined as an EF >50%; a secondary outcome was a combined outcome of subsequent heart failure (HF), admission, and death. Of 720 patients, 172 (24%) had an LVEF of <50% prior to PVI. The mean LVEF pre‐PVI was 41±6% (median 43%, range 20% to 49%). Forty‐three patients (25%) had LGE (25 [58%] ischemic), and the extent of LGE was 7.5±4% (2% to 19%). During follow‐up (mean 42 months), 91 patients (53%) had recovery of LVEF, 68 (40%) had early recurrence of AF, 65 (38%) had late AF, 18 (5%) were admitted for HF, and 23 died (13%). Factors associated with nonrecovery of LVEF were older age, history of myocardial infarction, early AF recurrence, late AF recurrence, and LGE. In a multivariable model, the presence of LGE and any recurrence of AF had the strongest association with persistence of LV dysfunction. Additionally, all patients without recurrence of AF and LGE had normalization of LVEF, and recovery of LVEF was associated with reduced HF admissions and death. Conclusions: In patients with AF and LV dysfunction undergoing PVI, the absence of LGE and AF recurrence are predictors of LVEF recovery and LVEF recovery in AF with associated reduction in subsequent death and heart failure.